Mandibular First Molar with a Single Root and Single Canal - Sooriaprakas, Chandrasekaran (Hindawi Publishing Corporation, 2014)
Successful endodontic management of mandibular first molar with a single root and single canal is diagnosed with the aid of dental operating microscope and multiple angled radiographs. In addition all the mandibular molars and premolars were single rooted on either side.